![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a) -6x + 3(7 + 2x)
= -6x + 21 + 6x
= (-6x + 6x) + 21
= 21
b) 15y - 5(6x + 3y)
= 15y - 30 - 15y
= (15y - 15y) - 30
= -30
c) x(2x + 1) - x2(x + 2) + (x3 - x + 3)
= 2x2 + x - x3 - 2x2 + x3 - x + 3
= (2x2 - 2x2) + (x - x) + (-x3 + x3) + 3
= 3
d) x(5x - 4)3x2(x - 1) ??? :V
Bài 2:
a) 3x + 2(5 - x) = 0
<=> 3x + 10 - 2x = 0
<=> x + 10 = 0
<=> x = -10
=> x = -10
b) 3x2 - 3x(-2 + x) = 36
<=> 3x2 + 2x - 3x2 = 36
<=> 6x = 36
<=> x = 6
=> x = 5
c) 5x(12x + 7) - 3x(20x - 5) = -100
<=> 60x2 + 35x - 60x2 + 15x = -100
<=> 50x = -100
<=> x = -2
=> x = -2
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: \(f\left(x\right)=x+7x^2-6x^3+3x^4+2x^2+6x-2x^4+1\)
\(=7x+9x^2-6x^3+x^4+1\)
\(=x^4-6x^3+9x^2+7x+1\)
\(f\left(-a\right)=\left(-a\right)^4-6\left(-a\right)^3+9\left(-a\right)^2+7\left(-a\right)+1\)
\(=a^4+6a^3+9a^2-7a+1\)
Vậy...
![](https://rs.olm.vn/images/avt/0.png?1311)
Khi P(x) + Q(x) ta đc
\(\left(9x-4x^3+3x^4-6x^2+1\right)+\left(4x^3-9x+5x^2-3x^4+1\right)\)
\(9x-4x^3+3x^4-6x^2+1+4x^3-9x+5x^2-3x^4+1\)
\(x^2+2\)
Ta có : \(C\left(x\right)=x^2+2=0\)
\(x^2=-2\)(vô lí)
![](https://rs.olm.vn/images/avt/0.png?1311)
1)3x4-5x3y+6x2-10xy+2
=(3x4-5x3y)+(6x2-10xy)+2
=x3(3x-5y)+2x(3x-5y)+2
=x3.0+2x.0+2
=0+0+2
=2
2) x5-2010x4+2010x3-2010x2+2010x-2020
=x5-(2009+1)x4+(2009+1)x3-(2009+1)x2+(2009+1)x-2009-11
=x5-(x+1)x4+(x+1)x3-(x+1)x2+(x+1)x-x-11
=x5-x5-x4+x4+x3-x3-x2+x2+x-x-11
=-11